Uterine Artery Embolization on Serum β-HCG Levels, Fertility Function and Clinical Efficacy in Patients With Cesarean Uterine Scar Pregnancy - Zhu, Wenyang; Zhang, Xiaofang; Liu, Chang; Liu, Yang; Xu, Wei (Frontiers in Surgery, 2022)
Objective: To analyze the therapeutic effect of UAE in patients with CSP delivered by cesarean section and the effect on serum β-HCG levels and reproductive function. Methods: 142 patients with CSP, The control group (n=71) received MTX with ultrasound monitoring after admission and the study group (n=71) was treated with UAE on basic of the control group. The effect of the two groups were compared at 1 month postoperatively, improvement in clinical symptoms (normalisation of β-HCG and normalisation of menstruation) and clinical outcome (normal pregnancy, recurrence of CSP) between the two groups, and the occurrence of postoperative complications. Results: Significant difference in recent efficacy between the two groups (P<0.05). Intraoperative bleeding, the time to get out of bed, the time to postoperative vaginal bleeding and the length of hospital stay after the operation for the study group were shorter compared with the control group (P<0.05). There was no statistically significant difference between the serum FSH, E2 and LH levels of the two groups at 1 month post-op and between the serum FSH, E2 and LH levels of the two groups at 1 month post-op compared with those pre-op (P>0.05). The serum β-HCG level of the two groups was lower at 1 month post-op compared to the pre-op period, and the study group was lower when compared against the control group (P<0.05). The time to return to normal serum β-HCG and the time to return to normal menstruation were significantly shorter in the study group when compared against the control group (P<0.05); Comparison of the recurrence rate of CSP in pregnancy for both groups was significantly different (P<0.05). The incidence of vomiting, fever, lower abdominal pain and other complications were lower in the study group (P<0.05). Conclusion: The treatment of CSP patients with UAE can reduce the amount of intraoperative bleeding and the duration of vaginal bleeding, promote the improvement of patients' clinical symptoms, have less impact on the disruption of patients' sex hormone balance, reduce patients' surgical risks to a greater extent, preserve patients' normal fertility, and have better application.